A lab test on the decision not to decide - Christian D. Schade; Avichai Snir (Business Research, 2020)
Decisions are often postponed even when future profits are not expected to compensate for the losses. This is especially relevant for financial and entrepreneurial disinvestment choices, as investors often have a disposition to hold on to losing assets for too long. We use an experiment with real real-options to study one possible behavioral motivation. Studies in psychology suggest that individuals have different styles of handling the stress involved in making decisions. We find that participants' styles of decision-making and risk aversion as well as the interaction of those can assist in predicting the likelihood that the participants will make investments and the timing of their disinvestment decisions. We also find the overall structure of the findings to be in line with a planner-doer model.
Keywords: D03; D81; L26; 650; Buck-passing; Conflict theory of decision-making Disinvestment decisions; Financial decisions; Player types; Realmonetary-stakes experiment; Risk aversion; Vigilance; Planner-doermodel